The LAW ON THE USE OF CRYPTOCURRENCY AS CURRENCY ACCORDING TO SHARIA ECONOMIC LAW - Ahmad Faizul Akbar Khatib; Kamaruzzaman; Riadhus Sholihin (JURISTA: Jurnal Hukum dan Keadilan, 2026)
This study examines the legal status of cryptocurrency as a medium of exchange under Islamic economic law. As digital currencies such as Bitcoin and Ethereum continue to gain acceptance in modern financial systems, their compatibility with Sharia principles has become a topic of ongoing academic debate. Using a qualitative approach based on a literature review, this study examines scholarly sources on cryptocurrency, Islamic commercial law, and the broader field of Islamic economics. This discussion highlights key concerns in Islamic jurisprudence, particularly those related to uncertainty (gharar), speculative risk (maysir), and the determination of clear and intrinsic value (qimah). The research findings reveal a spectrum of opinions among scholars, reflecting diverse interpretations among Islamic legal experts. Several scholars argue that the volatile and decentralised nature of cryptocurrency inherently makes it incompatible with established Shariah principles, due to its potential for excessive uncertainty, lack of clear value, and speculative behaviour. However, other scholars argue that, under certain conditions, cryptocurrency can be considered a permissible digital asset, provided it does not contain elements that contradict basic Sharia principles. This study concludes that although the use of cryptocurrency is not absolutely prohibited, a cautious approach is necessary to ensure compliance with ethical principles, social justice, and the broader public interest. Therefore, establishing a clear regulatory framework, along with authoritative fatwas, is essential to provide guidance and legal certainty for Muslim financial actors in digital transactions